HLA-vaccine transplantations for refractory leukemia: beyond double-unit cord blood - Leung, Wing; Seng, Michaela Su-Fern; Pham, Thi Ngoc Anh; Chong, Debbra; Tan, Ah Moy (Frontiers in Immunology, 2025)
Recent studies in double-unit cord blood transplantation have shown that when the patient (PT) and the losing unit (LU) share an HLA determinant mismatched against the winning unit (WU), leukemia relapse risk declines without added graft-versus-host disease (GvHD), suggesting a potential “HLA-vaccine” effect. Building on this principle, we treated five patients with refractory leukemia using graft combinations beyond cord–cord pairs, including haploidentical–cord (haplo-cord) and haploidentical–haploidentical (haplo-haplo) transplants, purposefully selected for predicted HLA-vaccine effects. All patients had measurable residual disease at transplantation and received reduced-intensity conditioning without total body irradiation. Engraftment occurred in all cases, with durable WU dominance and complete remission achieved within one month. Transient chimerism of the LU suggests a rapid, immune-mediated graft-versus-graft (GvG) and potentially graft-versus-leukemia (GvL) effect, triggered by shared, mismatched HLA allotypes. These findings imply that HLA-vaccine transplantation may be feasible across diverse graft pairings, offering a novel therapeutic avenue for refractory leukemia.